Functional characterization of AoPLL16 in salt tolerance regulated by AobHLH31 in Aquilegia oxysepala - Xuanyu Shen; Haihang Yu; Zhijia Chen; Shunyuan Yang; Tianshu Wang; Ying Qian; Yuan Meng; Yun Bai (Plant Science, 2026)

Mechanism of rice protein amyloid fibrils-induced structural changes of soybean protein during high-moisture extrusion: Focusing on multi-scale structural evolution - Jinming Ma; Kaizhi Li; Deyin Pan; Peng Wang; Mohamed E. Hassan; Wenyi Yang; Tianshu Zhang; Xiaoshuai Yu; Baoxin Lu; Zhigang Xiao (Food Research International, 2026)

Diverse crop rotation promoted crop yield via microbial networks in North China Plain - Shuting Yu; Yubin Zhao; Tianshu Wang; Shuihong Yao; Yang Gao; Jun Li; Xinhua Peng; Bin Zhang (European Journal of Agronomy, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Toward sustainable lithium recovery from brine: a hydrothermal carbon-coating strategy for minimizing Mn dissolution in ion-sieve adsorbents - Tianshu Bao; Congcong Li; Chenye Wang; Huiquan Li; Liangbin Li; Zhenhua Sun; Lili Yu; Xinjuan Hou; Aiping Peng; Ming Ye (Resources, Conservation and Recycling, 2026)

NCOA4-mediated ferritinophagy regulates AgNP-induced ferroptosis in lung cells - Rui Zhang; Haitao Yang; Menghao Guo; Shuyan Niu; Yu Ma; Xin Shen; Liqing Wu; Chenyu Liu; Mengjing Cui; Tianshu Wu; Yuying Xue (Food and Chemical Toxicology, 2026)

Machine learning-based diagnosis of uterine myomas and sarcomas using tumor-educated platelet transcriptomics: a retrospective multicenter study - Xudong Liu; Roujie Huang; Hua Yang; Yu Dong; Lei Li; Zhe Li; Jia Zeng; Qingxia Zhang; Yun Liu; Lei Zhang; Yidi Ma; Lin Zhang; et al. (Science Bulletin, 2026)

Green revolution gene drives adaptation of Arabidopsis to the extremely high altitude - Xing-Hui Hou; Yong-Chao Xu; Tianshu Sun; Yan-Bo Gong; Xin-Tong Li; Guang-Teng Jin; Yu-Tao Bian; Yi-Ni Liu; Juan Jiang; Xiao-Min Niu; Hongya Gu; Ya-Long Guo (Science China Life Sciences, 2025)

Does the establishment of China's national innovation demonstration zone for sustainable development enhance urban sustainable competitiveness?—Policy effects assessment based on multi-period difference-in-differences models - Tianshu Yu; Shuxin Mao (Journal of Environmental Management, 2024)

Similarity of Chinese and Pakistani oral microbiome - Xiaofang Sun; Binghua Han; Qian Han; Qiaoling Yu; Sijie Wang; Jie Feng; Tianshu Feng; Xiaoshan Li; Shiheng Zhang; Huan Li (Antonie van Leeuwenhoek, 2024)

Oxidative stress-activated Nrf2 remitted polystyrene nanoplastic-induced mitochondrial damage and inflammatory response in HepG2 cells - Menghao Guo; Yunjing Li; Shuyan Niu; Rui Zhang; Xin Shen; Yu Ma; Liqing Wu; Tianshu Wu; Ting Zhang; Meng Tang; Yuying Xue (Environmental Toxicology and Pharmacology, 2024)

Research on autonomous decision-making technology for once-through steam generator - Ren Yu; Cheng Li; Wenmin Yu; Xiaosen Song; Tianshu Wang (Annals of Nuclear Energy, 2023)

In situ polymerization of polypyrrole in oil body for efficient solar-driven freshwater collection - Hongxiang Liu; Tianshu Zou; Xingyu Cui; Miao Ding; Biao Zhang; Xiaodong Yang; Yu Han; Shuwei Nie; Yuan Zhang; Enze Wang; Lili Wang; Yan Cheng; et al. (Chemical Engineering Journal, 2023)

Insight into the dynamics of drinking water resistome in China - Mian Gul Hilal; Binghua Han; Qiaoling Yu; Tianshu Feng; Wanghong Su; Xiangkai Li; Huan Li (Environmental Pollution, 2023)

Effect of chlorogenic acid on lipid metabolism in 3T3-L1 cells induced by oxidative stress - Libo Liu; Chenyi Zhang; Min Zhai; Tianshu Yu; Mengqi Pei; Peng Du; Aili Li; Jiayi Yan; Chun Li; Guofang Zhang (Food Bioscience, 2023)

Changes in the m6A RNA methylome accompany the promotion of soybean root growth by rhizobia under cadmium stress - Xue Han; Jialin Wang; Yu Zhang; Youlin Kong; Huiying Dong; Xuezhen Feng; Tianshu Li; Changjun Zhou; Jidong Yu; Dawei Xin; Qingshan Chen; Zhaoming Qi (Journal of Hazardous Materials, 2023)

Localization of QTL for cold tolerance at the germination stage of rice (Oryza sativa L.) using recombinant inbred lines - Liangzi Cao; Shukun Jiang; Guohua Ding; Tongtong Wang; Liangming Bai; Jinsong Zhou; Yu Luo; Tianshu Xia; Hui Jiang; Kai Liu; Xueyang Wang; Guang Yang; et al. (Genetic Resources and Crop Evolution, 2022)
The cold tolerance of germinating direct-sown rice ( Oryza sativa L.) has an increased rate of emergence, which ensures vigorous seedling growth. Research on QTL localization for cold tolerance at the germination stage can assist in molecular marker-assisted selection and enhance breeding efficiency. In this study, 94 populations of recombinant self-incompatible lines from Heigu and Ha 9366 were selected to investigate germination rates at low temperatures. It was found that two QTL loci (qLTG-3 and qLTG-12) were located at different germination times on chromosomes 3 and 12, respectively. The two QTLs at three different germination times, located using QTL, accounted for 21.3–25.9% of the phenotypic variation. Moreover, a reciprocal effect was detected between the two QTLs. The double QTLs increased the germination rate by 22–27% in this population. Additionally, qLTG-12 improved cold tolerance at the seedling stage. The results of this study might provide the materials and molecular markers for future molecular marker-assisted breeding for cold tolerance at the germination stage.

Bioinformatic analysis of the complete genome sequence of Pectobacterium carotovorum subsp. brasiliense BZA12 and candidate effector screening - Yufei Huang; Changyuan Liu; Hui Wang; Tianshu Guan; Li Liu; Shuyi Yu (Journal of Plant Pathology, 2019)

Microsatellite records for volume 8, issue 2 - Dareen Almojil; Maria Cristina Arias; Rochelle R. Beasley; Yiyong Chen; Rulon W. Clark; Yinghui Dong; Zhiguo Dong; Natalie Forsdick; Elaine Françoso; E. González-Ortegón; A. M. González-Tizón; Linsheng Gui; et al. (Conservation Genetics Resources, 2016)